Understand the Meaning of Togetherness in Credit Cooperative Financial Management - Lucy Sri Musmini; Ni Luh Gede Erni Sulindawati; Gede Adi Yuniarta; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The principle of togetherness in cooperatives can be interpreted as joint work by all members of the cooperative. In cooperative financial management, it is important to prioritize cooperative ideals in the aspect of togetherness. This study aims to understand the meaning of togetherness in Swastiastu Credit Cooperative's financial management. This research was conducted by exploring the understanding of the meaning of togetherness inthe financial management of the Swastiastu Credit Cooperative. This phenomenological qualitative research aims to understand the response to the existence of humans/society, as well as experiences that are understood in interacting. Data collection is done by interview, observation, and documentation. Research data analysis consists of data organization, reading data, creating narratives, and participant experience reports. The results of the study show that the meaning of togetherness is to prioritize solidarity and participation of cooperative members to build cooperatives and prioritize members